2019
DOI: 10.1111/jfs.12697
|View full text |Cite
|
Sign up to set email alerts
|

A new cost‐effective process for limitation of microbial growth in fish fleshes: Wrapping by aluminum foil coated with electrospun nanofibers

Abstract: The primary aim of this study was to obtain a cost‐effective nanofiber (NCNF) on the surface of aluminum foil. The main aim of the study was to investigate the microbial quality parameters of fish flesh wrapped by aluminum foil coated with NCNF. NCNF having 128.98 nm average diameter and −2.26 mV zeta potential was successfully obtained. NCNF was utilized to delay the rapid increase in total viable bacteria (TVB), psychrophilic bacteria (TPBc), yeast and mold (TYMc), and lactic acid bacteria (LABc) growth in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…The initial count of H 2 S‐producing bacteria in puffer fish was about 2.92 log 10 CFU/g and WAEW+MAP puffer fish had significantly lower ( p < .05) counts than other samples at any of the storage time points (Figure 1c). LAB is an important part of natural microflora of fish and known as producing organic acids during cold storage (Ceylan, ). The initial LAB counts of the samples treated with/without WAEW were 2.25 and 1.73 log 10 CFU/g (Figure 1d) and reached to 7.98, 6.88, 6.03, 7.49, 6.58, and 5.09 log 10 CFU/g for AP, VP, MAP, WAEW+AP, WAEW+VP, and WAEW+MAP on the 18th day, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The initial count of H 2 S‐producing bacteria in puffer fish was about 2.92 log 10 CFU/g and WAEW+MAP puffer fish had significantly lower ( p < .05) counts than other samples at any of the storage time points (Figure 1c). LAB is an important part of natural microflora of fish and known as producing organic acids during cold storage (Ceylan, ). The initial LAB counts of the samples treated with/without WAEW were 2.25 and 1.73 log 10 CFU/g (Figure 1d) and reached to 7.98, 6.88, 6.03, 7.49, 6.58, and 5.09 log 10 CFU/g for AP, VP, MAP, WAEW+AP, WAEW+VP, and WAEW+MAP on the 18th day, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Abdou & Osheba (2012) reported that chitosan‐based nanoparticle limited the increase in TPB growth in fish fingers. Ceylan (2019) also noted that 0.0432 g nisin and 0.72 × 10 −4 g curcumin in a nano‐system delayed (up to 38%) the rapid TPB count in fish flesh stored at cold (4°C). Also, the nisin application delayed the rapid TPB count of sea bass ( Dicentrarchus labrax L.) fillets stored at 4 ± 2° (Uçar, Özoğul, Özoğul, Durmuş, & Köşker, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Levrek (Dicentrarchus labrax) [62] Nanoteknoloji Tabanlı Gökkuşağı alabalığı (Oncorhynchus mykiss) [63] Nanoteknoloji Tabanlı Gökkuşağı alabalığı (Oncorhynchus mykiss) [64] Nanoteknoloji Tabanlı Gökkuşağı alabalığı (Oncorhynchus mykiss) [65] Nanoteknoloji Tabanlı Gökkuşağı alabalığı (Oncorhynchus mykiss) [66] Nanoteknoloji Tabanlı Gökkuşağı alabalığı (Oncorhynchus mykiss) [67] Nanoteknoloji Tabanlı Gökkuşağı alabalığı (Oncorhynchus mykiss) [68] Nanoteknoloji Tabanlı Uskumru (Scomber scombrus) [69] Nanoteknoloji Tabanlı Gökkuşağı alabalığı (Oncorhynchus mykiss) [70] Nanoteknoloji Tabanlı Gökkuşağı alabalığı (Oncorhynchus mykiss) [71] Nanoteknoloji Tabanlı Karides (Macrobrachium rosenbergii) [72] Nanoteknoloji Tabanlı Tilapia fillets [73] Nanoteknoloji Tabanlı Restructured fish surimi [74] Nanoteknoloji Tabanlı Morina (Gadus morhua) [75] Sonuç…”
Section: Nanoteknoloji Tabanlıunclassified